National Assembly: An Empty Promise to Democracy - Koompong Noobanjong (My University, 2018)
Throughout history, architecture and urban design have been manipulated to serve politics. Capitals and capitols have become grand symbolic tools for the state, which should be understood in terms of their political and cultural contexts that helped bring them into being.
Accordingly, by presenting a multi-dimension critical inquiry of the National Assembly in Bangkok, Thailand, this paper argues via semiology, or a study of signs that the design of the Assembly fails to signify its original purpose: democratic ideology and practice. Ironically, however, such symbolic deficiency precisely captures the reality of democracy in Thailand. Here, democracy does not function merely as an ideology, but as a political discourse full of incongruity, paradox, manipulation, and deception.
In addition, through a critical urban study, this article reveals that the obscurity of the Assembly both in Thai architectural literature and in the urban fabric of Bangkok exemplifies the true state of the legislative branch of the government. A lack of integration between the Assembly and the physical condition of Bangkok notably the Rajadamnoen Avenue, ‘ the corridor of power,’ further demonstrates that the parliament is a rather weak and neglected institution. Significant political policies and decisions are formed and madeelsewhere. The parliamentary system acts merely as a tool for self-legitimization and authority-preservation in a game of power politics in Thailand.
Keywords: The Symbolic; Southeast Asian Sociopolitical Studies